The Discourse of Female Photojournalists: The Imbalance between Remunerated Labor and Maternity as a Professional Calling - Silva, Nathalia Cunha da; Gonçalves, Elizabeth Moraes (Brazilian journalism research, 2018)
This article aims to understand how female photojournalists see maternity within the profession in the contemporary world through the use of a study on the cultural and historical influence of gender roles on the performance and development of female photojournalists in the city of São Paulo. A qualitative methodology was adopted using semi-structured interviews. The interviews were conducted with nine female photojournalists from three different age groups who work both formally and informally. For the purposes of this study, we selected only the parts of the interview where the interviewees referred to their role of mother and professional. The analysis was based on a discursive approach, with theoretical support from French Discourse Analysis. The results show the influence gender roles have on forming symbolic barriers that connect having a career with an imbalance between paid work and maternity. O artigo objetiva compreender como as mulheres fotojornalistas percebem a maternidade dentro da profissão na contemporaneidade por meio de um estudo sobre a influência cultural e histórica dos papéis atribuídos de gênero na atuação e desenvolvimento feminino no fotojornalismo paulistano. A metodologia empregada é qualitativa, com uso de entrevista do tipo semiaberta. As entrevistas foram realizadas com nove mulheres que têm o fotojornalismo como principal atividade, com relações de trabalho formais e informais, divididas em três grupos etários. Para este texto foram selecionadas apenas as falas em que as entrevistadas faziam referência ao papel de mãe e profissional. O procedimento de análise seguiu uma abordagem discursiva, com subsídios teóricos na Análise do Discurso de linha francesa. Os resultados apontam a influência dos papéis atribuídos aos gêneros sobre a configuração de barreiras simbólicas que atrelam a permanência na carreira à exigência de um desequilíbrio entre trabalho remunerado e a maternidade. El artículo objetiva comprender cómo las mujeres fotoperiodistas perciben la maternidad dentro de la profesión en la contemporaneidad por medio de un estudio sobre la influencia cultural e histórica de los roles socialmente asignados de género en la actuación y el desarrollo de mujeres en el fotoperiodismo de la ciudad de Sao Paulo. La metodología empleada es cualitativa, con uso de entrevista del tipo semiabierta. Se entrevistó a nueve mujeres que actúan en el fotoperiodismo, con relaciones de trabajo formales o informales. Ellas han sido divididas en tres categorías de edad. Para este texto se seleccionaron sólo las palabras en las que las entrevistadas se referían al papel de madre y profesional. Los resultados apuntan a la influencia de los papeles atribuidos a los géneros sobre la configuración de barreras simbólicas que atrevan la permanencia en la carrera a la exigencia de un desequilibrio entre trabajo remunerado y maternidad.